Remedial measures for developmental strategies limiting economic biomass production in mango (Mangifera indica L.) with special reference to 'Sensation' - Oosthuyse, S. A.(Steven Andrew) (Stellenbosch : Stellenbosch University, 2012)
Dissertation (Ph. D. Agric.) -- University of Stellenbosch, 1995.